2010
DOI: 10.1089/jpm.2009.0370
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning and Hospice Enrollment: Who Really Makes the Decision To Enroll?

Abstract: These data indicate that some patients are not actively involved in the decision to enroll in hospice and that others, often physicians and family members, are making these decisions for the patient collaboratively. These data support the need for early education and interventions that assist patients and families in discussing ACP preferences and the need for greater understanding of how involved patients want to be with the decision to enroll in hospice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…Other research indicates that it is important to involve the patient in the decision-making process because patients differ in their treatment preferences and need for personal control (27). In our study, only 17% of participants reported that the final decision was made by medical staff alone, slightly lower than the proportions reported in previous studies (23,26,28). This difference may be due to cultural differences of the society.…”
Section: Discussioncontrasting
confidence: 90%
“…Other research indicates that it is important to involve the patient in the decision-making process because patients differ in their treatment preferences and need for personal control (27). In our study, only 17% of participants reported that the final decision was made by medical staff alone, slightly lower than the proportions reported in previous studies (23,26,28). This difference may be due to cultural differences of the society.…”
Section: Discussioncontrasting
confidence: 90%
“…40 Furthermore, almost half (49%) of family members of patients who died in one universityaffiliated hospice (n = 165) reported that the patient was not involved in hospice enrollment decisions. 27 Interventions to improve the timing and appropriateness of hospice referral to maximize the full benefits of hospice must include patients and their families. The association we found between educational attainment discordance of spouse and hospice use may be reflective of socioeconomic status, health literacy, realistic expectations about death, or knowledge about hospice.…”
Section: Discussionmentioning
confidence: 99%
“…16 While lack of hospice utilization or underutilization may be attributable to documented differences in patient characteristics (e.g., diagnosis, race, ethnicity, and income [17][18][19][20][21][22], and geographic region (e.g., hospice resources available, variation in services hospices provide [23][24][25] ), the decision-making process regarding hospice enrollment is often based within the family unit. 22,[26][27][28][29] While the family has a crucial role in determining hospice utilization, little is known about how family characteristics are associated with the decision to use hospice.…”
Section: Introductionmentioning
confidence: 99%
“…Overall involvement of various disciplines, patients and family was high in the 18 ACP meetings that were documented. Hirschman, Corcoran, Straton, & Kapo (2010) found in their study of 165 hospice patients, nearly 65.5% had an AD. In this present study, only seven patients were receiving hospice care.…”
Section: Chapter 5 Discussionmentioning
confidence: 92%